Revision of African Neaspasia Diakonoff, 1989 and the related Conaspasia, n. gen. (Lepidoptera, Tortricidae) - Aarvik, Leif; Agassiz, David J.l. (Zootaxa, 2014)
The six species of Neaspasia Diakonoff present in mainland Africa are described and illustrated. Niphadophylax albonigra Razowski & Wojtusiak and N. sophrona Razowski & Wojtusiak are transferred to Conaspasia, new genus. Four new species are described: Neaspasia coronana Aarvik, new species, N. karischi Aarvik, new species, N. malamigambo Aarvik, new species, and Conaspasia congolana Aarvik, new species. Argyroploce orthacta Meyrick, Argyroploce brevisecta Meyrick, and Penthina brevibasana Walsingham are transferred to Neaspasia. Neaspasia rhodesiae Razowski & Brown is a junior synonym of Neaspasia orthacta (Meyrick), new combination. Genetancylis homalota Razowski and Rhopobota cornuta Razowski, both described from Oman, are transferred to Neaspasia. Genetancylis Razowski is synonymised with Neaspasia.